Genserai Bungai Studio-produser of sago ecobeads - Chan Kit Yok, Margaret (UiTM Sarawak, 2018)
Initiated in 2009, Sago Fiber Clay - A New Media for Ceramic Artwork subsequently won a Silver Medal in IID2010/January 2010, UiTM Series in Shah Alam. The product was then qualified to enter the final round in the Pertandingan Inovasi Zon Sarawak, Kategori Wanita, MOSTI from 23 to 24 October 2010. The team consisting of Dr. Wan Samiati Andriana Wan Mohamad Daud, Associate Professor Dr. Margaret Chan Kit Yok, Norazlin Abdullah, Susana William and Safrina Azmi received RM40.000 from the Ministry of Higher Education under the Fundamental Research Grant Scheme for the project entitled Sago Fiber Clay Plasticity Behaviour in Ceramic Artwork (2012 to 2014). Three publications were produced.